Centralized versus Decentralized External Financing, Winner Picking and Corporate Socialism - Clemens Löffler; Thomas Pfeiffer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Applying the Monti-Klein framework, we examine the optimal financing strategy of a fi rm that requires funding for individual projects at an imperfect credit market. In particular, we study under which circumstances the firm should raise debt for projects separately (decentralized funding) or jointly (centralized funding) and how this organizational choice af fects the selection and resource allocation among projects. We fi nd that it is optimal to decentralize funding when competition at the credit market and the fi rm s level of equity are both either rather low or rather high. In this case, funding the strongest projects is optimal. For intermediate values of competition and equity, centralized funding is optimal. In this case, bundling strong projects with weak projects can be optimal (corporate socialism). All these funding strategies serve winner picking, i.e. the firm shifts disproportionately more funds to the pro table projects. In contrast to previous literature, winner picking and corporate socialism are not necessarily exclusive; rather, corporate socialism allows winner picking more aggressively.
Keywords: D21; L13; L22; 330